Rectangular spiral microstrip patch antenna integrated with LED for Wifi application / Mohd Syafiq Amari - Amari, Mohd Syafiq (2014)
This thesis investigates the characteristic of a rectangular spiral microstrip patch antenna integrated with Light Emitting Diode (LED) for Wifi application. The antenna was designed at 2.4 GHz and Genetic Algorithm (GA) technique was used to optimize the position of LED between the spirals. The performances of spiral antenna in term of return loss, gain and radiation pattern was verified through simulation by using Computer Simulation Technology (CST) Microwave Studio. The antenna was fabricated on FR4 substrate and was measured by Vector Network Analyzer (VNA) to demonstrate the capability and potential of the antenna.